Building blocks of a flip-chip integrated superconducting quantum processor. (1st July 2022) - Kosen, Sandoko; Li, Hang-Xi; Rommel, Marcus; Shiri, Daryoush; Warren, Christopher; Grönberg, Leif; Salonen, Jaakko; Abad, Tahereh; Biznárová, Janka; Caputo, Marco; Chen, Liangyu; Grigoras, Kestutis; et al.
Abstract: We have integrated single and coupled superconducting transmon qubits into flip-chip modules. Each module consists of two chips—one quantum chip and one control chip—that are bump-bonded together. We demonstrate time-averaged coherence times exceeding 90 μs, single-qubit gate fidelities exceeding 99.9%, and two-qubit gate fidelities above 98.6%. We also present device design methods and discuss the sensitivity of device parameters to variation in interchip spacing. Notably, the additional flip-chip fabrication steps do not degrade the qubit performance compared to our baseline state-of-the-art in single-chip, planar circuits. This integration technique can be extended to the realisation of quantum processors accommodating hundreds of qubits in one module as it offers adequate input/output wiring access to all qubits and couplers.